Kajian Problem Based Blended Learning sebagai Bentuk Implementasi Kurikulum Merdeka - Yahya, Fahmi; Arianto, Fajar (Indonesian Journal of STEM Education, 2022)
The learning process in the Merdeka Campus curriculum is one of the manifestations of student-centered learning, which is essential. In this curriculum, educators are given the freedom to implement more interactive and collaborative learning, as well as to use a variety of learning resources. The learning process in the Merdeka curriculum can be more flexible, not only face-to-face in the classroom, but also online through e-learning. This study was conducted to discuss learning reviews in accordance with the Merdeka curriculum from various theories. It then describes how problem-based learning (PBL) is integrated into blended learning in higher education, which is referred to as problem-based blended learning (PB2L). The results of the study show that this model is in line with the demands of the Independent Campus curriculum. PB2L combines face-to-face learning with online learning (synchronous and asynchronous) based on problems. This model can develop students' independence in seeking and discovering knowledge through reality and field dynamics, using real problems, utilizing technology, requiring social interaction, collaboration, and self-management to achieve learning outcomes.